Four quadrant single phase matrix converter / Siti Zaliha Mohammad Noor - Mohammad Noor, Siti Zaliha (2008)
In this work the Single-phase Matrix Converter (SPMC) is investigated as a basic four—quadrant single-phase converter with basic DC chopper operation. This is then extended to the operation of a single-phase inverter; without any change in the basic converter topology except with the switch control sequence. An outline of the basic principles of operation is defined. This follows the development of a computer simulation model using MATLAB and PSpice to study the basic behaviour. This is then verified on an experimental test-rig in the laboratory. Uniform pulse width modulation (UPWM) was used for the DC chopper control, whilst the well-known Sinusoidal pulse width modulation (SPWM) was used in inverter control. IGBTs are used for its power circuits, with Xilinx FPGA at the heart of its control electronics employing the use of digital techniques. Investigations into basic loads in operation are carried out to ascertain the behaviour. It presented that the SPMC is capable of performing four-quadrant operation as a basic DC chopper and an inverter; theoretically developed, conceived and successfully realized complete with safe commutation strategies.